From School Leadership to Community Leadership. (13th May 2015) - Eden, Devorah
Abstract: The aim of this literature case-study review is to present the unique solutions taken by principals of schools with socially marginalized student populations to overcome these problems. This is a review of three qualitative case studies of principals: (1) a principal of a Jewish school with children of migrant workers who were ignored by the State; (2) principals in a Jewish-Arab city who organized to act against city-hall corruption; (3) the struggle of Arab high school principals against favoritism in the appointment of teachers. The principals initiated pedagogical innovations to promote their students' achievements. When encountering resistance from school environment, they cooperated with local organizations for financial support. Then they struggled to change local and state laws and regulations by mobilizing the media, the legal and political systems and Third Sector organizations. Most principals acquiesce to authorities' demands. These principals defied the system thus redefining their role from organizational (school) leaders to community leaders. Principals should view their work as political in nature and form their own association to support each other.